PENDIDIKAN KEARAH PEMBENTUKAN KARAKTER - Yunarti, Yuyun (JURNAL TARBAWIYAH, 2014)
Education for human life is pramery or absolute need which should be has long life, without education is imposibble for a thousand human can life to be with they want to do and happiness based on life futuristics. The goal of education not only a culture switching process andÂ transfer of knowladge transfer of value itâs mean that education beside ofswitch and tranmissions, education also near to with the develope process and personality or society characters building te highess atitude for the learner have to has optimal education.Caracter Education not based on memorizing and verbality knowladge. Caracter education as the attitude education which habitual action and educator dicipline principle, parents, ledears, and society who large enviromnet fo the child caharecters. School is one of institution wich to bring out fo do character education.Â Formal education is point mainÂ to do life education characters and also prefer to educators models. Caharecters as characteristics thinks and atituted for every individu for life and do a coorporative with familly environment, society, and nation. The goodÂ character individu is the indiviadu who can make deccision and can to responsible for every his deccisson.